2012
DOI: 10.1016/j.ejvs.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The European Society for Vascular Surgery Guidelines for Carotid Intervention: An Updated Independent Assessment and Literature Review

Abstract: The ESVS guidelines that refer to carotid stenting not only remain valid but also have been further strengthened by the latest available clinical data. An update of these guidelines including all of the recent evidence is needed to provide an objective and up-to-date interpretation of the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 42 publications
1
49
0
6
Order By: Relevance
“…On the contrary, the American Society for Vascular Surgery [24] published an update of their 2008 guidelines 2 months after the publication of AHA guidelines stating that their guidelines were more circumspect with regard to the role of CAS and a more supportive role of CEA. Kakisis et al [25] reviewed the 2009 European Society for Vascular Surgery guidelines and also found that CEA is preferable to CAS for the majority of symptomatic patients. However, both guidelines of the vascular societies did not recommend CAS for asymptomatic patients.…”
Section: Randomized Trials Of Cea Vs Casmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the American Society for Vascular Surgery [24] published an update of their 2008 guidelines 2 months after the publication of AHA guidelines stating that their guidelines were more circumspect with regard to the role of CAS and a more supportive role of CEA. Kakisis et al [25] reviewed the 2009 European Society for Vascular Surgery guidelines and also found that CEA is preferable to CAS for the majority of symptomatic patients. However, both guidelines of the vascular societies did not recommend CAS for asymptomatic patients.…”
Section: Randomized Trials Of Cea Vs Casmentioning
confidence: 99%
“…According to the latest guidelines [2,24,25] , BMT is an essential part of the treatment for all patients with CS whereas symptomatic patients with more than 50% stenosis and highly selected patients with more than 60% asymptomatic stenosis should be considered for CR. In spite of disputable data from CAS and CEA, each of them is associated with their own high-risk features, which are summarized in table 3 .…”
Section: Decision-making On Management Of Carotid Stenosismentioning
confidence: 99%
“…Higher volume hospitals may have more vascular surgeons with a particular interest in carotid surgery as well as specialist anesthetists and better short-term results [13] . Currently, European and US guidelines do not specify a minimum volume or experience for CEA practice [14,15] . The present report does not demonstrate significantly lower complication rates amongst centers with more experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…One in five patients suffer from ischemic stroke caused by internal carotid artery stenosis (1). The available level I evidence recommends surgery as currently the best option for symptomatic patients (2).…”
Section: Introductionmentioning
confidence: 99%